VIII. Milletlerarası Türkoloji Kongresi, 30 Eylül - 04 Ekim 2013, İstanbul (İstanbul)
4 c. (xxx, 749 s., 24 s. resim (renkli) ; xxxii, 733 s., 24 s. resim (renkli) ; xxxiii, 1102 s., 24 s. resim (renkli) ; xxxv, 1038 s., 24 s. resim (renkli))